find the product

This problem can be rewritten as (3a+2)(3a+2)(3a+2) then we multiply by distribution and combine like terms

3a*3a = 9a^2

3a*2 = 6a

2*3a = 6a

2*2 = 4

so far we have 9a^2 + 12a + 4 (3a+2)

9a^2*3a = 27a^3

12a*3a = 36a^2

4*3a = 12a

9a^2*2 = 18a^2

12a*2 = 24a

4*2 =  8

So we have 27a^3 + 36a^2 + 18a^2 + 12a + 24a + 8

Simplify this to 27a^3 + 54a^2 + 36a + 8

by Level 4 User (9.5k points)
2.3*1.87+3*3.12
by    i I Kinda Get It Im Still Fuzzy ON The (3a+2) To The 3rd Power.....!.....Thing........ ..........'''''''''''',,,,,,,,,,,,,,,,..........''''''

by
i will like to fine. y is seven more than nine times x
by
hi i would like to solve the equation 3/4m=7-1/4m (note that the slashes represents fraction bars ..thanks
by
(7 x10^5) x (2 x 10^2)
by
(3a + 2)^3 =  (3a+2)(3a+2)(3a+2)

multiply( 3a+2)(3a +2)  suggest multiplying in VERTICAL format

(9a^2+12a+4)

multiply the above by (3a+2) again  being careful to keep your like terms lined up

27^3+54a^2+36a+8
by
Simplify using positive exponents: (3t 5) -2
by
5 to the third power -12 divided by 3
by
163/4 hr work 2 day + 123/4  hr for 2 days how many hour did you work
by
Answers to choose from: -16x36y16, 2x36y16, 16013y8, 16x36y16.
by
UNDERSTANDING EXPONENANTS
by Level 1 User (140 points)
q.27a^3+54a^2+36a+8

ans.=27a^2[a+2]+36a+8+64-64

=27a^2[a+2]+36[a+2]-64

=[27a^2+36]+[a+2]-64
by
r(x) = x to second power minus 1 over x to 4 power minus 16  and sketch the graph and dot - cross analysis complete the analysis function
by
2+8/2*3-1+3*3*3
by
explain why 4.6,4 3/5 and 23/5 are all the same
by
2a(a – 5) + 4(a – 5)
by
You have to multiply the first two terms using FOIL (First, Outer, Inner, Last). Once you have the result (trinomial / 3 term answer), take the first part of the trinomial and multiply it by the remaining term (3a + 2), then do the same for the second and third part of the trinomial. Once you have those answers, line them up from greatest power to least power and combine like terms.

Hope this helps some and doesn't make it more confusing for you.
by

1/2 + 2/3= 7/6

by
7)3(x+x+1+2)
by
x-y=2

xy=15
by
by
8 over 10 = what over 100
by
what is the earth
by
7 - 4 + 5 * 0 + 1
by
27a cubed plus 8
by
9a^2+15a+6
by
9a^2+12a+4
by
27a^3 + 54a^2 + 36a +8 just use the shortcut. 1. Cube the first term. 2. Thrice the product of the square of the 1st term and the last term. 3. Thrice the product of the 1st term and the square of the last term. 4. Cube the last term.
by
What is 2 over 7 plus 3 over 7
by
2-1^2+ (2-1)^3 evaluate
by
12 . . ____________________________________________
by
How many times does 2 go in to 2
by
8886
by
deffinition of fourth-power-free integer
by
(3a+2)3

=(3a)3 + (3*(3a)2*2) + (3*3a*(2)2 + (2)3

= 27a3+54a2+36a+8
by
VII-ATIS,

Kahit ano sagot

di Ko po alam

ay ambot

Yolanda Scandal
by
6844
by

فرض مراقبة عدد 2 في السلامية 7اساسي

by
y2-7-2 and y2+4=
by
5x-6x+x
by
Simplify using the correct order of operations 5(2-4)+6÷3
by
First I did what was in the parentheses.
Since he did not give the value of the variable which is a.

So I plugged in 3. Now 3 times 3 equals 9 + 2 =11.Now I did 11 too the power of 3.11 times 3 =33 times 3 = 99

by

Let 3a=A, and 2=B, so (3a+2)³=(A+B)³ ··· Eq.1    Use standard polynomial form for (A+B)³:

(A+B)³=A³+3A²B+3AB²+B³ ··· Eq.2    Plug A=3a, and B=2 into Eq.2.   We have:

(3a+2)³=(3a)³+3(3a)²(2)+3(3a)(2)²+(2)³

=27a³+54a²+36a+8 ··· Eq.3

CK: Plug a=1 (or any number) into Eq.3.  LHS=(3x1+2)³=5³=125

RHS=(27x1)³+54x(1)²+36x(1)+8=27+54+36+8=125   Thus, LHS=RHS    CKD

by
3a+8
by
why does parentesis affect the outcome of a problem with exponets?
by